PEMODELAN ARSITEKTUR SISTEM INFORMASI PERHOTELAN DENGAN KERANGKA KERJA TOGAF ADM - Selviana Yunita; Wing Wahyu Winarno; Asro Nasriri (Informasi Interaktif, 2019)
The development of information technology towards the era of the internet of things require all aspects of life to implement and utilize information systems, one of those aspect is hotel management, to achieve its vision and mission. The tickle hotel is a two star hotel located in the middle of Yogyakarta city. Today the tickle hotel has implemented an information system to support its business processes, but the current information system has not been integrated with other division, so there are several problems. One of the problems is data stored separately and requires manual data transfer to collect all data, and obviously slower the staff performance. To resolve these problems, an integrated information system architecture is needed so that each division can be interconnected. To building an information system architecture, it requires a careful planning and based on company's business needs, because the development of information technology is a kind of investment that expected to provide appropriate results. This information system architecture modeling uses the TOGAF framework as a guide in compiling information system architecture. The results of this study are in the form of a blueprint for information systems portfolios that are in line with business needs and have been verified by the Tickle hotel IT manager and experts in the IT field. Keywords: TOGAF, Hotel, Information System Architecture, Enterprise Architecture